On Public Teachers’ Intention to Stay in the Profession and its Profile Determinants - Casinillo, Leomarich F; Cortes, Jessica; Salabao, Analita; Hungo, Melbert (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Teachers are considered committed to their job if they remain in their profession and accept professional responsibilities. This article aimed to investigate the public teachers' willingness to remain in their jobs and identify some determinants that causally affect it. The study employed a developed research instrument based on an existing research paper in the literature to gather primary data from cross-sectional public teachers. This study used random sampling to select the required participants of the survey and utilized appropriate statistical methods (descriptive and inferential statistics) to summarize and extract information from the data gathered. This study involved five schools as subjects. Some descriptive analysis was utilized such as frequencies and percentages to give a description of the gathered data and extract relevant information. The results showed that female public teachers are more likely to stay in the profession as opposed to male teachers. In addition, employment status and job position are significant factors that influence teachers to stay in their profession. Conclusively, public teachers who are satisfied with their current income and work assignments are more likely economically secure and willing to serve. Hence, the study suggests that the government must support public teachers regarding incentives and benefits, salary increases, and other resources that improve their well-being and productivity, and avoid employee turnover.